Social Media Portfolio (ENT 530): InternetNetizen / Putera Muhammad Hakimi Zaini - Zaini, Putera Muhammad Hakimi (2021)
‘InternetNetizen’ is a small business that operates online and sells tie-dye socks. ‘InternetNetizen’ is a business owned by Putera Hakimi. Social media such as Facebook, Instagram, and WhatsApp for any inquiries or transactional processes about the product also promote, communicate, and interact with the customers. After that, ‘InternetNetizen’ decided to use online social media platforms such as Facebook, Instagram, and WhatsApp. Also, WhatsApp is following an inter or social media algorithm and gets positive feedback and engagement from social media users. Then, as an aspect of its 'InternetNetizen' individuality and style of marketing strategies and to attract customers, 'Internet Netizen' has its posting aesthetic by taking care of its quality of graphic design and quality of content. Then, ‘InternetNetizen’ is also a business that is fully operated by using an online platform without a physical store and based on Malacca. Malaysia. Next, ‘InternetNetizen’ tie & dye socks are sold at reasonable prices and easily owned by all. Furthermore, InternetNetizen tie & dye socks use a very high-quality tie & dye colour that does not easily tear when washed and the colour durable. While the selection of socks is also important, ‘InternetNetizen’ considers this by using 100 percent cotton-based socks. And 'InternetNetizen' makes every effort to improve business quality in terms of customer service, packaging, shipping, etc.